Peritumoral granulomatous reaction in endometrial carcinoma: association with DNA mismatch repair protein deficiency, particularly loss of PMS2 expression. Issue 3 (22nd June 2018) - Stewart, Colin J R; Pearn, Amy; Pachter, Nicholas; Tan, Adeline
Abstract : Aims: The observation of peritumoral granulomatous reactions (PGRs) in two endometrial carcinomas (ECs) with a PMS2‐deficient/MLH1‐intact expression pattern led us to investigate whether PGRs in EC were specifically associated with DNA mismatch repair (MMR) protein deficiency, particularly PMS2 loss. Methods and results: Hysterectomy specimens from 22 MMR protein‐intact and 54 MMR protein‐deficient ECs were reviewed with specific attention to the presence of a PGR and a tumour‐associated lymphoid reaction [including tumour‐infiltrating lymphocytes (TILs) and stromal lymphoid infiltrates]. The MMR protein‐deficient ECs included 22 cases with combined MLH1/PMS2 loss, 11 with combined MSH2/MSH6 loss, 11 with isolated MSH6 loss, and 10 with PMS2 loss but intact MLH1 staining (including the two 'index' cases). Overall, PGRs were identified in seven of 54 (13%) MMR protein‐deficient ECs, five of which showed a PMS2‐deficient/MLH1‐intact immunophenotype; three of these patients had germline PMS2 mutations and one additional patient had a germline MSH6 mutation. None of the MMR protein‐intact tumours showed a PGR. Although five of the seven PGR‐positive ECs had a high‐grade histological component, six were stage I. Most ECs with PGRs also showed TILs and stromal lymphoid reactions, similarly to MMR protein‐deficient ECs in general. Conclusions: MMR protein‐deficient ECs, particularly those with PMS2 loss, occasionally show PGRs in addition to stromal lymphoid infiltrates and TILs. Therefore, PGRs could be considered to constitute a histological prompt for consideration of Lynch syndrome. The potential prognostic significance of PGRs in EC requires further study.